2018
DOI: 10.1128/iai.00019-18
|View full text |Cite
|
Sign up to set email alerts
|

PDL-1 Blockade Prevents T Cell Exhaustion, Inhibits Autophagy, and Promotes Clearance of Leishmania donovani

Abstract: Leishmania donovani is a causative pathogen of potentially fatal visceral leishmaniasis (VL). Therapeutic agents are available; however, their use is limited because of high cost, serious side effects, and development of antimicrobial resistance. Protective immunity against VL depends on CD4+ Th1 cell-mediated immunity. Studies have shown that progression of VL is due to exhaustion of T cells; however, the mechanism involved is not clearly understood. Here, we examined the role of PD1/PDL-1 in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 44 publications
(51 reference statements)
1
46
1
Order By: Relevance
“…With regard to helminth infection, it was shown that cestode Taenia crassiceps infections in mice induce macrophages alternatively activated with strong suppressive activity involving the PD‐1/PD‐L1 pathway . Blockade of the PD‐1/PD‐L1 pathway during infections with certain pathogens such as Toxoplasma restored exhausted CD8 + T cell response, and promoted brain leucocyte infiltration and diminishes cyst burden in another mouse infection model . It was also shown that blocking PD‐L1 signalling in Leishmania donovani ‐infected mice resulted in restoration of protective type 1 responses by both CD4 + and CD8 + T cells, which resulted in a significant decrease in the parasitic burden .…”
Section: Introductionmentioning
confidence: 97%
“…With regard to helminth infection, it was shown that cestode Taenia crassiceps infections in mice induce macrophages alternatively activated with strong suppressive activity involving the PD‐1/PD‐L1 pathway . Blockade of the PD‐1/PD‐L1 pathway during infections with certain pathogens such as Toxoplasma restored exhausted CD8 + T cell response, and promoted brain leucocyte infiltration and diminishes cyst burden in another mouse infection model . It was also shown that blocking PD‐L1 signalling in Leishmania donovani ‐infected mice resulted in restoration of protective type 1 responses by both CD4 + and CD8 + T cells, which resulted in a significant decrease in the parasitic burden .…”
Section: Introductionmentioning
confidence: 97%
“…41 Similarly, experiments conducted on the blocking of PDL-1 accessory proteins expressed on the surface of T cells in inbred BALB/c mice led to a significant reduction in the parasite load and increased the levels of protective type CD4 þ and CD8 þ T cell-mediated immune response. 42 Histopathology VL, a distinctive immunosuppressive disease, is characterised by severe hepatomegaly and splenomegaly during the acute phase of illness. A successful treatment not only shifts the immune response toward the adaptive type but also preserves normal architecture of the severely affected organs.…”
Section: T Cells and Subsetsmentioning
confidence: 99%
“…Single bilayers positive of LC3 seem to surround apoptotic Leishmania major with the consequence of dampening the parasite-directed CD4 T cell response ( Crauwels et al, 2015 ). Reducing T cell exhaustion by blocking PD1-L signaling inhibited autophagy and reduced Leishmania donovani burden ( Habib et al, 2018 ).…”
Section: Autophagy and Leishmaniamentioning
confidence: 99%